NEGATIVE IMPACTS OF TOURISM ON THE ENVIRONMENT - Manikateva, Vanya Georgieva (Europa del Este Unida, 2021)
This publication points out the negative effects of tourism on the environment. Its aim is to see tourism not only as a boon to the economy, prosperity and employment, but also as a complex, multi-stakeholder industry. The purpose is to find a mechanism for proper tourism management, through which to achieve a positive role in the social, cultural, economic, natural and political development of the destination. Otherwise, its uncontrolled development can lead to many harmful effects on the natural resources, consumption patterns, pollution and social structures.